Facilitating Research and Collaborative Learning in a Somali Community - Connie L. Clark; Bernita Missal (The University of Alabama, 2022)
Due to an increasingly diverse world, healthcare researchers should consider collaborative research within a cultural community in order to provide holistic care for all patients. One of the key steps in cultural research is establishing relationships with leaders within that cultural community. Because the Somali group is such a large cultural group in the state of Minnesota, two Caucasian nurse researchers from an academic institution used several methods to connect and build trust within the Somali community in preparation for a study designed to discover and understand the birth experience of immigrant Somali new mothers. Through the process of conducting research within the Somali community, several lessons were learned and a number of surprises were revealed. Following the research, a continued relationship with the community resulted in collaborative learning opportunities. This collaboration is of mutual benefit to healthcare providers and the cultural community.